Embracing Muslims in a Catholic Land: Rethinking the Genesis of Islam in Mexico - Benzion, Jonathan, (Muslim Minorities ;, 2022)
"This study presents a contrasting hypothesis concerning the genesis and development of Islam in Mexico than the one generally held across academic spheres and current historiography. It demonstrates that Colonial and Early Independent Mexico and Islam may have as well known about the existence of each other. However, within the chronological framework in which the Viceroyalty of Nueva España lived and developed there were social hindrance, geopolitical imperatives and theological impediments and cosmovisions - in both sides of the Atlantic - that created the quasi-perfect circumstances for the Islamic tradition and Mexico not to really meet. This book provides new angles of study on the theme, and with it, new historiographical approaches"--